2018
DOI: 10.1111/jocs.13608
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage solutions, gene therapy, and antiproliferative agents on endothelial function and saphenous vein graft patency

Abstract: Vein graft failure remains a major concern after coronary artery bypass graft operations, and is initiated by loss of endothelial cell integrity. Preservation of saphenous vein grafts in the optimal solution after meticulous harvesting can limit the endothelial damage. Despite both experimental and clinical results in favor of buffered solutions, normal saline is still the most widely used solution. This review examines the literature to identify the most optimal storage solutions currently available for vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Of course, disadvantages of the vein graft include lower graft patency as compared with arterial grafts. Several attempts have been introduced to overcome the poor graft patency of SVGs - pharmacotherapy [ 11 ] , buffered storage solutions [ 12 ] , gene therapy [ 13 ] , external stenting [ 14 ] , and harvesting technique [ 8 ] . NT-SVG is one of the solutions to improve graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, disadvantages of the vein graft include lower graft patency as compared with arterial grafts. Several attempts have been introduced to overcome the poor graft patency of SVGs - pharmacotherapy [ 11 ] , buffered storage solutions [ 12 ] , gene therapy [ 13 ] , external stenting [ 14 ] , and harvesting technique [ 8 ] . NT-SVG is one of the solutions to improve graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that reendothelialization is beneficial to prevent the failure of vein transplantation, but so far there is no treatment to promote this process (20). our previous studies demonstrated that, in the rabbit vein transplant model, a high level of cell proliferation was observed in the vascular wall of vein graft on day 7 after surgery (26).…”
Section: Discussionmentioning
confidence: 99%
“…S100a8 and S100a9 genes in vein grafts were upregulated in a rabbit vein grafts model. Thus, it was speculated that S100a8/9 protected the endothelial integrity of vein grafts, which play an important role in preventing intimal hyperplasia (20). in addition, raGe could represent a potential target in the mTorc2 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to conduit choice and technique of vein harvesting, the role of storage solution has been implicated as an important contributing factor to venous graft failure . In the hours following surgery, saphenous venous grafts are exposed to ischaemic reperfusion injuries, with reduced levels of NO production leading to proinflammatory states . The standard of practice has been to store the products of harvesting in heparinized 0.9% normal saline (NS) before implantation.…”
Section: Endoscopic Harvestingmentioning
confidence: 99%